OSGeo - Open Source Geospatial Foundation - Di Leo, Margherita; Ghisla, Anne; Di Stefano, Massimo (GEOmedia, 2012)
L'esigenza nata verso la fine del 2005 di selezionare ed organizzare più di 200 progetti FOSS4G porta alla nascita nel Febbraio2006 di OSGeo (the Open Source Geospatial Foundation), organizzazione internazionale la cui mission è promuovere lo sviluppo collaborativo di software libero focalizzato sull'informazione geografica (FOSS4G). Open Source Geospatial Foundation (OSGeo) The Open Source Geospatial Foundation (OSGeo) is a not-for-profit organization, created in early 2006 to the aim at sup-porting the collaborative development of geospatial open source software, and promote its widespread use. The founda-tion provides financial, organizational and legal support to the broader open source geospatial community. It also serves as an independent legal entity to which com-munity members can contribute code, funding and other resources, secure in the knowledge that their contributions will be maintained for public benefit. OSGeo also serves as an outreach and advocacy organization for the open source geospa-tial community, and provides a common forum and shared infrastructure for im-proving cross-project collaboration. The foundation's projects are all freely available and useable under an OSI-certified open source license. The Italian OSGeo local chapter is named GFOSS.it (Associazione Italiana per l'informazione Geografica Libera).